Acceptability of Squash ‘Desal (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
One of the Filipinos’ specialties is to prepare nutritious food because they put premium nutritional value to furnish their bodies with adequate nourishment for growth to maintain and repair cells and tissues. Essential for good health is an outweighing factor in the selection of a nutritionally adequate diet and also an indication not only of the physical state of an individual but also of his general attitude toward work, play, and life itself. Appropriate nourishment gives the feeling of well-being. Hence, a variety of menus makes an individual skillful in planning such kinds of menus. Baking is regarded as the best method of cooking to retain the nutritive value of food. Baked products are not only rich in calories but also in protein, fats, minerals, and vitamins. Given that they do not contain much cooking oil, baked products are digestible. They also have a long shelf life. It also allows an individual to be creative. The baker who enjoys his work tries new recipes from time to time, thereby improving the quality of his/her products. The researchers used a descriptive research design. The researchers also used a random sampling technique to choose the respondents. According to the researchers’ findings, squash ‘desal has a good taste, aroma, texture, and appearance. Thus, this product can be accepted in the market. The product is not only good for health but can also become one's business at home. Based on the information gathered by the researchers, the product will be acceptable in the market. The respondents also recommended improving the product’s size. The researchers need a good marketing strategy to introduce their product in the market.
Keywords: acceptability, squash pandesal, baked products